Factors Influencing Intention to Use Social Media Sites for Holiday Destination Selection by the Young Generation - Matikiti-Manyevere, Rosemary; Hattingh, Johannes (African Journal of Hospitality, Tourism and Leisure June 2020, Vol 9, No 3, pp. 302-318, 2020)
The main objective of the study was to examine the factors that influence attitude towards usage of social media for holiday destination selection by the young generation, specifically university students and to explore the antecedents of behavioural intention to use social media sites. A structured questionnaire was used to gather data for this study, yielding a total of 350 responses suitable for analysis. Regression analysis was employed to test the hypotheses. The results revealed that social presence, perceived ease of use, perceived usefulness and perceived enjoyment all positively influence attitude towards use of social media sites. Revealed by the results also is that perceived behavioural control, subjective norm and attitude also positively influence behavioural intention. Social media developers should develop sites, which are attractive, fun and exciting so that the young generation can be attracted. Moreover, destination marketers must ensure that all the important information is posted on their social media sites pages. Studies have been conducted on the usage of social media sites for searching travel related products, but limited research has been done focusing specifically on the usage of these sites by the young generation, such as university students in the South African context.
Article
Keywords: Media sites; Holiday; Destination; Young generation; Intention